PROCESSING JACKFRUIT SEED WASTE (Artocarpus heterophyllus lamk) INTO AN ALTERNATIVE FOOD SOURCE FOR TEMPE - Fadhel Rizky Suryawan; Zuhra Salsabilla; Azmira Lasari Tanjung; M. Farand Farensyah Garal; Susheila Yuliawati (CV. Radja Publika, 2025)
This study aims to determine how to process jackfruit seeds (Artocarpus heterophyllus lamk) into a food source of tempeh without using soybeans, and to assess its feasibility as an alternative to soybean tempeh. The background of this study is based on Indonesia's high dependence on soybean imports, which causes the price of tempeh raw materials to increase. Jackfruit seeds were chosen because they have high nutritional content such as carbohydrates, protein, vitamins, and minerals, as well as their abundant availability. Which is suitable as a substitute or alternative to jackfruit seeds. This study used a quantitative research method with an experimental approach through the fermentation process of jackfruit seeds using Rhizopus oligosporus yeast. The results showed that jackfruit seed tempeh has good physical and organoleptic characteristics, with a solid shape, soft but compact texture, grayish white color, slightly sweet savory taste, and a distinctive aroma of tempeh. The fermentation process for two days at room temperature (28–32 °C) resulted in even mycelial growth and optimal fermentation. In terms of nutrition, jackfruit seed tempeh contains quite high protein and fiber so it has the potential to be a nutritious and affordable alternative food. Thus, jackfruit seeds have the potential to be a substitute for soybeans in the production of tempeh, while also supporting food diversification and reducing Indonesia's dependence on soybean imports.